Methodologies for Assessing Disease Tolerance in Pigs - Nakov, Dimitar; Hristov, Slavcha; Stankovic, Branislav; Pol, Françoise; Dimitrov, Ivan; Ilieski, Vlatko; Mormede, Pierre; Hervé, Julie; Terenina, Elena; Lieubeau, Blandine; Papanastasiou, Dimitrios K.; Bartzanas, Thomas; et al. (Frontiers in Veterinary Science, 2019)
Features of intensive farming can seriously threaten pig homeostasis, wellbeing and productivity. Disease tolerance of an organism is the adaptive ability in preserving homeostasis and at the same time limiting the detrimental impact that infection can inflict on its health and performance without affecting pathogen burden per se. While disease resistance can be assessed measuring appropriately the pathogen burden within the host, the tolerance cannot be quantified easily. Indeed, it requires the assessment of the changes in performance as well as the changes in pathogen burden. In this paper, special attention is given to criteria required to standardize methodologies for assessing disease tolerance in respect of infectious diseases in pigs. The concept is applied to different areas of expertise and specific examples are given. The basic physiological mechanisms of disease tolerance are reviewed. Disease tolerance pathways, genetics of the tolerance-related traits, stress and disease tolerance, and role of metabolic stress in disease tolerance are described. In addition, methodologies based on monitoring of growth and reproductive performance, welfare, emotional affective states, sickness behaviour for assessment of disease tolerance, and methodologies based on the relationship between environmental challenges and disease tolerance are considered. Automated Precision Livestock Farming technologies available for monitoring performance, health and welfare-related measures in pig farms, and their limitations regarding disease tolerance in pigs are also presented. Since defining standardized methodologies for assessing disease tolerance is a serious challenge for biologists, animal scientists and veterinarians, this work should contribute to improvement of health, welfare and production in pigs.